The code is here

int getEqualSumSubstring(string s) { int i=0,j=i,foundLength=0; for(i=0;i<s.length();i++) { for(j=i;j<s.length();j++) { int temp = j-i+1; if(temp%2==0) { int leftSum=0,rightSum=0; string tempString=s.substr(i,temp); // printf("%d ",tempString.length()); for(int k=0;k<temp/2;k++) { leftSum=leftSum+tempString[k]-48; rightSum=rightSum+tempString[k+(temp/2)]-48; } if((leftSum==rightSum)&&(leftSum!=0)) if(tempString.length()>foundLength) foundLength=tempString.length(); } } } return(foundLength); }I wanted to know how the calculation of temp = i+j-1 is done ? how on paper or by examples he could get that equation. I tried a lot but I couldn't get it.

**Edited by AhmedCoeia, 10 December 2012 - 11:12 PM.**